Human rights and the care of the self - Lefebvre, Alexandre 1979- (Duke University Press, 2018)
The care of the self -- The juridical subject as ethical subject : Wollstonecraft on the rights of man -- Critique of human rights and care of the self -- Human rights as spiritual exercises : Tocqueville in America -- Human rights as a way of life : Bergson on love and joy -- On human rights criticism -- An ethic of resistance I : Roosevelt and the universal declaration of human rights -- An ethic of resistance II : Malik and the universal declaration of human rights -- Human rights education